Timeliness of lung cancer care in Victoria: a retrospective cohort study. Issue 2 (1st February 2016) - Evans, Sue M; Earnest, Arul; Bower, Wendy; Senthuren, Meera; McLaughlin, Peta; Stirling, Rob
Abstract: Objective: To assess factors associated with second‐line delays in the management of patients diagnosed with lung cancer. Design, setting and participants: A retrospective cohort study, conducted in six public and two private Victorian hospitals, of 1417 patients aged 18 years or more who were diagnosed between July 2011 and October 2014 with an incident case of lung cancer identified by International Classification of Diseases, 10th revision codes (C34.0–C34.9, Z85.1, Z85.2) on the basis of either a clinical or pathological diagnosis. Outcome measures: Time intervals between referral, diagnosis and initial definitive management. Results: The median time from referral to diagnosis was 15 days (interquartile range [IQR], 5–36); from diagnosis to initial definitive management, 30 days (IQR, 6–84); and from referral to initial definitive management, 53 days (IQR, 25–106). Factors that were significantly associated with delay between referral and initial definitive management include declining or not being referred to palliative care (hazard ratio [HR], v patients referred for palliation, 0.73; 95% CI, 0.62–0.86; P < 0.001), and being treated in a public hospital (HR, v patients managed in a private hospital, 0.55; 95% CI, 0.48–0.64; P < 0.001). The median time from referral to initial definitive management in public and private hospitals was 61 days (IQR, 35–118) and 30 days (IQR, 13–76) respectively; 48% of patients in public hospitals waited longer than the British National Health Service target of a maximum 62 days between referral and first definitive treatment. Conclusion: There are significant delays at various stages of the patient journey after referral for initial definitive management. Having a greater understanding of these delays will enable strategies to be developed that improve the timeliness of care for patients with lung cancer.